From the Logic of Modern Science to an Integral Hermeneutics. Following an Analogy belonging to Francis Bacon - Munteanu, Cristinel (Acta Universitatis Danubius. Communicatio, 2023)
Although I will also refer to an influent analogy made by Francis Bacon and to R.G. Collingwood’s explanation concerning it, however, my article will mainly deal with John Dewey’s ideas in this regard. John Dewey developped a special logic, which he named the theory of inquiry. Dewey’s logic can be considered, actually, an integral hermeneutics, since it also examines the meanings which man creates when interpreting nature. According to Dewey, sciences are systems of related meanings obtained through inquiry. An inquiry follows a certain pattern, by transforming, in a controlled way, an indeterminate, confusing situation into a determinate one, which, thus, gets meaning. A problematic situation can be clarified only if it is transposed linguistically in our mind. How can we get, by means of inquiry, to the individual meaning of a concrete situation, by using the meanings already acquired in a certain field? Dewey states that individual meaning can be obtained as a result of articulating a judgment, which arises from a chain of logical propositions. They can be either (i) existential propositions (which extract the relevant data from concrete situations) or (ii) conceptual propositions (which direct inquiries towards the best way to solve the given situations). These propositions collaborate. The existential ones are similar to the workers who (selectively) excavate ancient objects from ruins. The conceptual ones are like the archeologists who establish the meaning of the objects found by the workers.